Comparison of the quality of life in individuals with spinal cord injury wearing either reciprocating gait orthosis or hip knee ankle foot orthosis: a cross-sectional study. (18th August 2021) - Barati, Kourosh; Kamyab, Mojtaba; Kamali, Mohammad
Abstract: Background: The quality of life (QoL) for patients with spinal cord injuries (SCI) is lower than that for healthy individuals. The main purpose of prescribing orthoses for these individuals is to improve their mobility and QoL. The hip knee ankle foot orthosis (HKAFO) has been the conventional choice for such patients, whilst the reciprocating gait orthosis (RGO) is a more contemporary option. Although the impact of these two types of orthoses on the biomechanics of walking has been previously evaluated in patients with SCI, there has been no specific comparison of their relative effects on QoL. Objectives: This study aimed to evaluate the Sickness Impact Profile (SIP-68) QoL questionnaire's total score and its sub-scores in patients with SCIs wearing either RGOs or HKAFOs. Methods: This study was performed on 22 participants (11 participants wearing RGOs and 11 wearing HKAFOs). QoL scores were evaluated in each group of patients using the total and sub-scores from the SIP-68 questionnaire. Results: There were no significant differences in the total SIP-68 scores between the RGO and HKAFO groups ( p  = .57). However, emotional stability and emotional independence sub-scores were significantly lower for the RGO users than for the HKAFO users ( p  = .03 and p  = .01), respectively. Conclusions: Based upon this preliminary study, participants wearing RGOs or HKAFOs had similar QoL scores. However, those wearing RGOs may experience better emotional stability, communication, and emotional independence. This preliminary study does not provide definite conclusions since a large randomized control trial is required to compare the effects of these orthoses on the QoL scores in patients with SCIs. Implications for rehabilitation: Our main aim in the current investigation was to shed light on the question that does the biomechanical superiority of the RGO to the HKAFO leads to better quality of life in SCI subjects who are using RGO. Regarding the fact that the primary goal of rehabilitation of people with SCI is to improve their quality of life, it seems that the more complicated newer orthosis (RGO) has no difference with the older type (HKAFO) in achieving the rehabilitation goals. More studies will in fact be necessary to find a definitive answer for this important question. According to the findings of our study, it seems to be more appropriate to prescribe RGO for male participants with higher body weight.